2015
DOI: 10.1038/mp.2015.81
|View full text |Cite
|
Sign up to set email alerts
|

Huntington’s disease cerebrospinal fluid seeds aggregation of mutant huntingtin

Abstract: Huntington's disease (HD), a progressive neurodegenerative disease, is caused by an expanded CAG triplet repeat producing a mutant huntingtin protein (mHTT) with a polyglutamine-repeat expansion. Onset of symptoms in mutant huntingtin gene-carrying individuals remains unpredictable. We report that synthetic polyglutamine oligomers and cerebrospinal fluid (CSF) from BACHD transgenic rats and from human HD subjects can seed mutant huntingtin aggregation in a cell model and its cell lysate. Our studies demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 42 publications
2
41
0
1
Order By: Relevance
“…CSF has recently been associated with seeding aggregation of mutant Huntingtin,35 and various components have been posited for use as clinical biomarkers 36. The EBM then predicts changes in the amygdala, optic chiasm, and third ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…CSF has recently been associated with seeding aggregation of mutant Huntingtin,35 and various components have been posited for use as clinical biomarkers 36. The EBM then predicts changes in the amygdala, optic chiasm, and third ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular work has previously shown that it is possible to seed the formation of puncta using polyQ proteins. 20,27 Furthermore, Serpionov and co-workers showed that HTTQ25 aggregation can be seeded and in turn seed the aggregation of other Q/N-rich proteins in yeast. 28 Our data show that for HTT ex1 this is a direct seeding effect in which the seed structure is almost entirely reproduced by the new fibril that is formed.…”
Section: Discussionmentioning
confidence: 99%
“…87 Furthermore, aggregates isolated from several HD transgenic mouse models seed the aggregation of pure polyQ peptides in vitro , 88 and seeding of mutant htt aggregation is also induced by cerebrospinal fluid from transgenic rats and human HD patients. 89 Aggregates of synthetic htt exon1-like peptides grown under conditions that promote different aggregation pathways have varying abilities to seed further aggregation. 38 This observation is interesting considering that, in a Drosophila model, polyQ amyloids formed in older flies more efficiently seeded in vitro aggregation than those derived from younger flies, 90 suggesting that aggregates formed in flies vary in their biophysical properties and perhaps aggregation mechanism as a function of fly age.…”
Section: Polyq-mediated Protein Aggregation Is a Complex Processmentioning
confidence: 99%